2017
DOI: 10.1073/pnas.1614364114
|View full text |Cite
|
Sign up to set email alerts
|

A pathway of targeted autophagy is induced by DNA damage in budding yeast

Abstract: Autophagy plays a central role in the DNA damage response (DDR) by controlling the levels of various DNA repair and checkpoint proteins; however, how the DDR communicates with the autophagy pathway remains unknown. Using budding yeast, we demonstrate that global genotoxic damage or even a single unrepaired double-strand break (DSB) initiates a previously undescribed and selective pathway of autophagy that we term genotoxin-induced targeted autophagy (GTA). GTA requires the action primarily of Mec1/ATR and Rad5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 68 publications
2
69
0
Order By: Relevance
“…The role of autophagy in carcinogenesis is context-dependent. It was demonstrated that the induction of autophagy is associated with DNA damage (55)(56)(57). Autophagy has been shown to regulate some of the DNA repair proteins after DNA damage (55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of autophagy in carcinogenesis is context-dependent. It was demonstrated that the induction of autophagy is associated with DNA damage (55)(56)(57). Autophagy has been shown to regulate some of the DNA repair proteins after DNA damage (55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that the induction of autophagy is associated with DNA damage (55)(56)(57). Autophagy has been shown to regulate some of the DNA repair proteins after DNA damage (55)(56)(57). One the other hand, some evidence has demonstrated that some DNA repair molecular have a crucial role in the initiation of autophagy (58,59).…”
Section: Discussionmentioning
confidence: 99%
“…Global genotoxic damage induces genotoxin-induced targeted autophagy (GTA). GTA is a selective pathway of autophagy and requires the ATG11 gene (Eapen et al, 2017). Unlike the comprehensive studies in yeast, there are a few reports about the roles of ATG11-mediated selective autophagy in filamentous fungi.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously characterized an Mec1-and Tel1-dependent pathway for DNA damage-induced autophagy (22). We speculated that Pds1 is a target of GTA since we had shown Pds1 localized to vacuoles following a DSB.…”
Section: Pds1 Localizes To the Vacuole Independently Of Autophagymentioning
confidence: 98%
“…Both the localization and adaptation defects were rescued by deleting the vacuolar protease Pep4 (14), which is also required for the maturation of other resident vacuolar proteases (20,21). These observations along with the identification of a DNA damage-induced autophagy pathway termed, Genotoxin-induced Autophagy (GTA) (22), led us to suspect that Pds1 was a target of GTA. Here we show that Pds1 is targeted to the vacuole independently of autophagy and instead requires components of the alkaline phosphatase transport pathway (ALP) (23).…”
Section: Introductionmentioning
confidence: 99%